2018
DOI: 10.1016/j.redox.2017.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted remodeling by vitamin C boosts sensitivity of Mycobacterium tuberculosis subpopulations to combination treatment by anti-tubercular drugs

Abstract: Bacterial dormancy is a major impediment to the eradication of tuberculosis (TB), because currently used drugs primarily target actively replicating bacteria. Therefore, decoding of the critical survival pathways in dormant tubercle bacilli is a research priority to formulate new approaches for killing these bacteria. Employing a network-based gene expression analysis approach, we demonstrate that redox active vitamin C (vit C) triggers a multifaceted and robust adaptation response in Mycobacterium tuberculosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 77 publications
2
46
2
Order By: Relevance
“…4 Vitamin C possibly has both pro-oxidant and antioxidant activities regarding mycobacteria (Table 1). [5][6][7][8][9][10] Biologically plausible hypotheses pertaining to the modulation of anti-TB drug efficacy by these activities are summarized as follows. The former activity might help in bacillary killing through the oxidative burst, 1,5 and the latter activity possibly in limiting the size of Mtb persister population, through inhibition of mycobacterial dormancy-related pathways 5-7 that likely include guanosine pentaphosphate ((p)ppGpp) signalling, as there is a structural analogy of vitamin C and guanosine diphosphate, the substrate for (p)ppGpp synthesis.…”
Section: To the Editorsmentioning
confidence: 99%
“…4 Vitamin C possibly has both pro-oxidant and antioxidant activities regarding mycobacteria (Table 1). [5][6][7][8][9][10] Biologically plausible hypotheses pertaining to the modulation of anti-TB drug efficacy by these activities are summarized as follows. The former activity might help in bacillary killing through the oxidative burst, 1,5 and the latter activity possibly in limiting the size of Mtb persister population, through inhibition of mycobacterial dormancy-related pathways 5-7 that likely include guanosine pentaphosphate ((p)ppGpp) signalling, as there is a structural analogy of vitamin C and guanosine diphosphate, the substrate for (p)ppGpp synthesis.…”
Section: To the Editorsmentioning
confidence: 99%
“…We have read with great joy the letter to the editor, written by Yew et al, which analyzes and compares several recent articles [1][2][3][4] showing the intimate relationship between Mycobacterium tuberculosis' (Mtb) redox status -mainly due to the presence of Reactive Nitrogen and Oxygen Species (RNOS) -and tubercular drug efficacy. Given the fact that tuberculosis (TB) is an infectious disease for which there is a limited arsenal of effective drugs, it is crucial to find new drugs or to somehow enhance pre-existing treatments.…”
Section: Aires Consejo Nacional De Investigaciones Científicas Y Técmentioning
confidence: 99%
“…Recently, similar results were shown by the same group that Vitamin C has dichotomous role in modulating antibiotic activity. It was found that co‐treatment of Vitamin C with INH and RIF leads to drug tolerance which increased their Minimum Inhibitory Concentration (MIC) by 32‐ to 128‐fold, but on the contrary, increased the cidal activity of PZA by fourfold . These findings suggest that the combination of Vitamin C with PZA significantly improves killing of Vitamin C‐induced dormant bacteria, and also efficiently negates Vitamin C‐induced tolerance to INH and RIF in both axenic culture and intracellular models.…”
Section: Introductionmentioning
confidence: 99%